THE PERSONALIZED IMMUNOGENOTYPIC PREDICTION OF HUMAN PREDISPOSITION TO OPHTHALMO-PATHOLOGY OF DIFFERENT GENESIS - V. I. Konenkov; A. V. Shevchenko; V. F. Prokof’ev; V. V. Klimontov; D. V. Chernykh; V. V. Chernykh; A. N. Trunov (Сибирский научный медицинский журнал, 2019)
The purpose of the study was to search high-informative genetic criteria of the personalized forecast at presence of the earliest feebly marked of clinical attributes of organum visus pathology development.Material and methods. The results of immunogenotypic survey of 403 persons, among which 102 patients with age-related macular degeneration (AMD) and 90 patients with diabetic retinopathy (DR), 211 patients of similar gender and age as control groups of comparison are submitted. The analysis of regulation locus polymorphism TNFА (rs361525, rs1800629 and rs1800630), IL1B (rs1143627), IL4 (rs2243250), IL6 (rs1800795), IL10 (rs1800872, rs1800872) genes, vascular endothelial growth factor gene VEGF (rs3025039, rs699947), matrix metalloproteinases genes MMP (rs2438650, rs3025058, rs3918242) in this groups has been carried out.Results and discussion. Two groups of parameters have been shown through comparison of combined genetic attributes frequencies in comparable groups with/or absence AMD. One of these groups is distributed with primary frequency among patients with AMD whereas another is distributed only among elderly with absence of clinical and tool attributes of disease. On the contrary the significant prevalence of the attributes positively associated with the pathology development over negatively associated attributes has been revealed among DR. The revealed genetic attributes specify mainly inflammatory character of DR, as against AMD in which prevail degenerate and sclerogenic processes.Conclusion. Thus, the results of received genetic researches show an opportunity to personify predisposition of the significant part of elderly patients to development of ophthalmo-pathology microangiopathy or degenerate genesis with the purpose of realization of purposeful preventive actions.